Respostas

A melhor resposta!
2014-03-01T23:42:01-03:00
A = 3 2
      5 4, então 
[ 3  2]  * [ a b] = [ 1 0 ]
 5 4 ]      [ c d ]  [ 0 1]
3a+2c=1     3b+2d=0
5a+4c=0     5b+4c=1

multiplica o de baixo por menos o de cima 
 3a+2c=1 * 5                  3b+2d=0 * -5
5a + 4c=0 * -3                 5b+4c=1 * 3

15a+10c=5                           -15b-10d=0
-15a-12c=0 corta o a              15b+12d=1 corta o b
--------------------                      ---------------------
-2c=5                                  2d=1
c=-5/2                                    d=1/2
 
substitui na eq. 3a+2c=1              subt na eq 3b+2d=0
3*a+2*c=1                                     3b+2(1/2)=0
3a+2*(-5/2)=1                               3b+1=0
3a-10/2=1                                    3b=0+1
3a-5=1                                          b=1/3
3a=1+5
a=6/3
a=2
                                               Demorei mas tá aí!!

1 5 1